1991
DOI: 10.1111/j.1600-0447.1991.tb03151.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of affective disorders in three Asian countries. II. Differences in prevalence rates and symptom presentation

Abstract: This study used standardized diagnostic criteria and method to investigate both prevalence rates and nature of symptoms of depressive disorders in three Asian centres--Nagasaki, Shanghai and Seoul. Of the patients who visited a psychiatric clinic in each of the 3 centres for the first time, over 20% suffered from depression. Unlike previous reported prevalence rates for Asian countries, these results suggest that rates in Asia may not be much lower than those reported in Western countries. Although prevalence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
16
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 4 publications
5
16
0
Order By: Relevance
“…HADS could be a suitable instrument for this purpose. Although there are cross-cultural differences in the prevalence of psychological distress such as major depression, phobic disorders, and alcohol abuse/dependence between Western countries and Asian countries, [24][25][26] the relationship between HADS and QLQ-C30 in the present study is close to that reported in other investigations. 14,31 This may also support the validation studies of the Japanese versions of HADS 7 and QLQ-C30, 10 respectively.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…HADS could be a suitable instrument for this purpose. Although there are cross-cultural differences in the prevalence of psychological distress such as major depression, phobic disorders, and alcohol abuse/dependence between Western countries and Asian countries, [24][25][26] the relationship between HADS and QLQ-C30 in the present study is close to that reported in other investigations. 14,31 This may also support the validation studies of the Japanese versions of HADS 7 and QLQ-C30, 10 respectively.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, it was of interest to find whether the associations would be reproducible in Japanese cancer patients, irrespective of crosscultural differences in the prevalence of psychiatric distress between Asian countries and Western countries. [24][25][26] Patients and methods…”
Section: Introductionmentioning
confidence: 99%
“…More than two-thirds of the emotional disorders were associated with complaints concerning the heart and liver. Nakane et al (1991) studied depressive disorders in China, Japan, and Korea, and found that rates of depressive disorders among these three Asian countries were similar to rates reported in Western countries. They reported that there was a difference in the types of depressive disorders and the presentation of symptoms between patients in these three countries.…”
Section: Expression Of Depression In Chinasupporting
confidence: 68%
“…Despite the fact that the 21-item HRSD is an established instrument also in transcultural studies on depres-sion [22,[82][83][84], our paper points to demands for adaptations to improve its applicability in such investigations: (1) for the assessment of the whole spectrum of ethical feelings, the HRSD needs an additional item for shame; (2) the definitions of feelings and delusions of guilt are lacking in (psychopathological) precision, and (3) the same holds good for the differentiation between hypochondriac anxiety and delusions. Moreover, proper ethnolinguistic studies could provide the basis for the development of special instruments for transcultural studies beyond the HRSD.…”
Section: Existence Of Depressive Delusions Of Guilt Only In Austriamentioning
confidence: 99%